Cattle milk and meat production and marketing systems and opportunities for market-orientation in Fogera woreda, Amhara region, Ethiopia - Anteneh, B.; Tegegne, Azage; Beyene, F.; Gebremedhin, Berhanu (International Livestock Research Institute, 2010)
This study was conducted in Fogera woreda, South Gondar Zone of the Amhara National Regional State in northwestern Ethiopia in 2005/06. The aim was to characterize cattle milk and meat production and marketing systems, identify the major constraints and provide development interventions for more market-orientation. Twelve kebeles were randomly selected (five from the Fogera plains and seven outside the plains) based on their potential for cattle milk and meat production. A total of 480 households were sampled from these kebeles and focus group discussion, personal observations and administration of semi-structured questionnaires on milk and meat production practices were employed. Only 12 (2.52%) of the respondents were female-headed households. About 98.8% of cattle milk and meat production was based on traditional husbandry using indigenous cattle breeds. The Fogera cattle is the major breed used and is mainly found in the Damote, Sendeye and Tigre mender villages. The main feed resources in the woreda are communal grazing land and crop residues of teff, rice, finger millet, barley, wheat, chickpea, field pea and maize. The communal grazing land currently accounts for about 9602.4 ha; out of which 3418.5 ha (35.6%) is infested by a noxious weed known as Asracantha longifolia (amykila). Over a period of two years, large area of communal grazing land has been transformed into crop farms, mainly to rice production, and this has apparently created severe feed shortage in the woreda. Flooding of the plains during the wet season from Gumara and Rib rivers further reduced the availability of grazing land. In addition, large number of animals are trekked from the highlands of Fogera and adjacent woredas of Dera and Estie to the plains during the dry season and this has resulted in inter-breeding of the Fogera cattle breed with highland zebus and has exacerbated the feed shortage. Rice husk, a by-product from rice polishers, is becoming an important feed resource. On average, about 35 kg of rice husk is produced from a quintal of rice. The major water resources are wells (48.8%), rivers (47.2%), lake (3%), ponds (2.3%) and tap water (0.2%). Cattle are watered once a day. Trypanosomiasis, facioliasis and schistosomiasis are the most prevalent diseases.